Effect of Selenium nanoparticles antioxidant on sperm parameters in mature and adult rats - Habibeh ghazanfarpoor; Ebrahim Talebi; Farangis Ghasemi; Marjan Haghigat Jahromi (Fasa University of Medical Sciences, 2014)
Background & Objective: Selenium is often caused selenoproteins, which is using in the construction of antioxidant enzymes that are necessary for the health of those cells which are subjected to oxidative stress-induced. Due to its antioxidant properties, selenium is an essential and rare element for spermatogenesis and sperm characteristics, especially in the late reproductive age. Therefore, in this study, the role of selenium nanoparticles was investigated on semen parameters in young and adult rats. Materials & Methods: Mature male Wistar rats (2-3 months old) and the adult ones (10-12 months), are divided into 4 groups where 5 animals per each group are put (control, testifier and experimental groups). The experimental rats received Selenium Nano particles through stomach tube for 35 days, each day different doses of 0.2 and 0.4 mg/kg of their body weight. . After this period, the semen parameters in both mature and adult rat were compared. Results: The spermatozoa count, sperm motility and viability, increased particularly in adult rats which used 0.04 mg/kg body weight nano selenium and the number of dead and damaged Spermatozoa are significantly reduced (p<0.05). The Percentage of sperm cell injury increased significantly in young rats in the group that received a dose of 0.04 mg of selenium nanoparticles. Conclusions: These findings suggest that administration of Nano-Selenium improves the sperm parameters during the spermatogenesis.